Beyond the Surface: Tracing the Evolution of Inflammatory Mechanism in Depression through Bibliometric Analysis - Xu, Zhang-Yang; Zhang, Ting; Gong, Hong; Zheng, Hong; Liu, Mei-Shan; Guo, Bing-Hang; Wang, Yun-Xia; Su, Wen-Jun (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2025)
BackgroundDepression is a common mental illness that has become a major economic burden worldwide. Recently, increasing evidence has highlighted the inflammatory mechanism of depression. In order to understand the research status of this field, this study used the bibliometric analysis method to overview the research content and progress, as well as analyze the development trend and limitations.MethodsIn this study, articles and reviews were included in the specific search strategy. The matched papers were exported from the Web of Science database. CiteSpace 6.3 R1 and Bibliometrix (R package) were utilized to generate bibliometric and knowledge maps.ResultsA total of 25,063 articles were included in this study. The number of publications in this field has gradually increased, especially in recent years. These papers come from 156 countries, led by the United States and China mainland. The leading research institution is the University of Toronto (Canada). Brain Behavior and Immunity is the journal with the most publications and the most frequently co-cited journals. Among 91,100 authors, Maes M has the most publications and co-citations. According to the keywords burst and co-cited reference analysis, the hotspots in the field in recent years include kynurenine, c-reactive protein, neuroinflammation, and gut microbiota.ConclusionAlthough abundant academic achievements have been made on the inflammatory mechanism of depression, there is still a long way to go before these research results can be applied to clinical practice. Strengthening international academic exchanges and cooperation may promote breakthroughs in this field.
Keywords: citeSpace